ST-segment elevation acute coronary syndrome in a child with Duchenne muscular dystrophy: a case report - Z. G. Tatarintseva; O. V. Babicheva; K. O. Barbuhatti (Российский кардиологический журнал, 2024)
Introduction. Duchenne muscular dystrophy is an X-linked muscle disorder caused by the dystrophin absence. This leads to the death of muscle cells and cardiomyocytes and their subsequent replacement with adipose and fibrous tissue. Clinically, this disease manifests itself as progressive muscle weakness and cardiomyopathy. We report a case of a young patient with acute myocardial injury without coronary artery occlusion due to Duchenne muscular dystrophy.Brief description. A 15-year-old male patient with Duchenne muscular dystrophy, no risk factors for coronary artery disease and known cardiac diseases presented with pressing chest pain. Electrocardiography showed ST segment elevation on the inferior and lateral walls. Given the pressing chest pain, electrocardiographic abnormalities and elevated cardiac biomarkers, an initial working diagnosis of acute myocardial infarction was made and the patient was taken to the catheterization laboratory for coronary angiography, which demonstrated normal cardiac anatomy and coronary arteries without hemodynamically significant stenoses. The patient was discharged from the hospital on day 14 with a final diagnosis of Duchenne muscular dystrophy cardiomyopathy and recommendations for perindopril 5 mg daily and bisoprolol 5 mg daily.Discussion. Frontline practitioners should be aware of the high prevalence of car diomyopathy in patients with Duchenne muscular dystrophy, which increases with age. Cardiac biomarkers may be chronically elevated in this disease. However, a high suspicion combined with echocardiography and magnetic resonance imaging may help in diagnosing acute myocardial injury in these cases. Based on this case, we discuss the dilemmas of management and follow-up of this complex group of patients.